Głos Solidarności . pismo KZ NSZZ "Solidarność" WSK "PZL-Mielec", no. 50, 1981 - NSZZ "Solidarność", [ed. board] (Związkowa Rada Nadzorcza NSZZ "Solidarność" WSK "PZL-Mielec", 1981)
Creation and circulation: For internal use; fter the introduction of the Martial Law, publication suspended in 1982-1988. Republished underground in 1989